PENERAPAN METODE PROBLEM SOLVING DAPAT MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V DI SDN 9 PANGKALAN NYIRIH KECAMATAN RUPAT - Indriyani, Indriyani; Lazim N, Lazim N; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This education is conducted because of the low of learning result of Math class V student of SD Negeri 9 Pangkalan Nyirih, KKM set at school, that is 65. From 20 students, reaching KKM 4 student while student who do not reach KKM is 16 students with average value average student (58.50%). To solve the problem then the researcher apply problem solving method, the purpose of this research is to improve student learning outcomes of SDN 9 Class V Pangkalan Nyirih Rupat District with the application of problem solving method, the result of research is average value of the average score of the students ability is 59%. Increased in cycle I by 72%. In cycle II also experienced an average increase of 77%. After applied method of problem solving mastery learn student increase to 90%. The teacher activity of the first meeting of the first cycle of the percentage is 50% with the sufficient category and at the second meeting of the first cycle the percentage increases to 54% with sufficient percentage and on the activity of the Cycle II teacher the first meeting of the percentage of 75% with the good category and at the second meeting increased to 91 % with very good category. The activity of the students at the first cycle meeting is the percentage is 50% with enough category, at the second meeting of the cycle I the percentage is 54% with enough category, the first meeting of second cycle of the percentage is 83% with good category, at the second meeting increased to 91% very good, from this research can be concluded that by applying problem soling method can improve the result of learning mathematics of student of class V SD Negeri 9 Pangkalan Nyirih.Keywords: problem solving method, mathematics learning result